Blended learning integration at Sabah’s Tertiary Institutions, Malaysia - Tracy Joann Stanlee; Wardatul Akmam Din; Chelster Sherralyn Jeoffrey Pudin; Suyansah Swanto (Global Academic Excellence, 2021)
21st Century era marks where internet and technology become a necessity throughout every aspects of life; added with current Covid-19 pandemic situation which hinders physical contact between humans to prevent the virus keep spreading. Eventually, traditional teaching approach requires to shift towards new norm that integrates technology in all courses, including English Language Courses, as well as to adhere the Standard Health procedure. This paper enlightened the benefits and challenges when implementing Blended Learning in the classroom efficiently among ESL educators and learners. This review paper was administered through appropriate vicarious data in previous studies form conducted by various researchers in English as Second Language (ESL). The findings revealed that Blended Learning incorporation brought advantages for both ESL educators and students when this 21st Century teaching strategies being incorporated in ESL classrooms. In addition, this paper may help students improve their learning achievement, as well as increase ESL educators’ self-efficacy to fully employ Blended Learning that leads to their advancement of their teaching quality skills, especially during Covid-19 pandemic era.